Herpes Zoster and Immunogenicity and Safety of Zoster Vaccines in Transplant Patients: A Narrative Review of the Literature - Wang, Lei; Verschuuren, Erik A. M.; van Leer-Buter, Coretta C.; Bakker, Stephan J. L.; de Joode, Anoek A. E.; Westra, Johanna; Bos, Nicolaas A. (Frontiers in Immunology, 2018)
This narrative review focuses on the herpes zoster (HZ) and its prevention in transplant patients.Varicella zoster virus (VZV) is highly contagious and distributed worldwide in humans. Primary VZV infection usually causes varicella and then establishes a lifelong latency in dorsal root ganglia. Reactivation of VZV leads to HZ and related complications such as postherpetic neuralgia. Age and decreased immunity against VZV are important risk factors for developing HZ. Transplant patients are at increased risk for developing HZ and related complications due to their immunocompromised status and the need for lifetime immunosuppression. Diagnosis of HZ in transplant patients is often clinically difficult and VZV-specific antibodies should be determined by serologic testing to document prior exposure to VZV during their pre-transplant evaluation process. Although antiviral agents are available, vaccination should be recommended for preventing HZ in transplant patients considering their complicated condition and weak organ function. Currently there are two licensed herpes zoster vaccines, of which one is a live attenuated vaccine and the other is a HZ subunit vaccine. Both vaccines have shown promising safety and efficacy in transplants patients and especially the subunit vaccine could be administered post-transplant since this vaccine does not contain any live virus. Larger studies are needed about safety and immunogenicity of HZ vaccines in transplant populations and extra efforts are needed to increase vaccine usage according to guidelines.